The Existence of Traditional Markets in the Face of Modern Markets - Nurul Yaqin; Rita Ambarwati; Sigit Hermawan (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The domination of Modern Markets over Traditional Markets has made it difficult for Traditional Markets to gain access to the economy, resulting in opportunities for monopolistic practices and dirty games for investors. Competition that occurs between Modern Markets and Traditional Markets is a familiar phenomenon, especially in the era of globalization and the rapid development of science. The aim of this research is to find out how the existence of traditional markets compares to the existence of modern markets in Wamena. The type of research used is a qualitative descriptive research method with a phenomenological approach with data sourced from observations and interviews with informants.